Antifungal Activity and Mechanism of Major Compound Isolated from Hexane Extract of Curcuma zedoaria - Chen, Zizhu; Wei, Yan; Li, Xue; Peng, Chenchen; Long, Zhangfu (Asian Journal of Chemistry, 2013)
The main compound of hexane extract from Curcuma zedoaria was purified using bioactive-guided silica gel column chromatography and high performance liquid chromatography in this study and the structure of the main compound was identified as curcumenol by spectroscopic methods, including high resolution mass spectra (HRMS), FTIR, 1H and 13C NMR spectroscopy. It was firstly authenticated that curcumenol derived from C. zedoaria showed higher and broad-spectrum antifungal activity against fungal phytopathogens, such as Fusarium graminearum, Phoma wasabiae, Plasmodiophora brassicae and Magnaporthe grisea while their minimal inhibition concentration were 0.5 1.0, 1.0, 1.0 mg mL-1, respectively. The antifungal activity was not affected by high or low pH values (from 2-10) or under different temperatures (from 30-80 ºC). Its antifungal mechanism was further investigated by comparing the ultrastructures of the experimental fungi using scanning electron microscope and transmission electron microscope and results showed that its antifungal activity was realized by means of destroying the cell-wall and influencing the nutrients circulation of the fungal phytopathogens.